Figurative Rhetoric about the Transiency of the World in the Qur'an: an Analysis of Tashbīh Qs. Al-Kahf [18]: 45 - Dika Purnama Aulia Rohma; Abdurrahman Al Kausar; M. Ibnu Wahid Al Huda; Ibnu Hajar Ansori; Daing Fuadi A. Kadir Tawajok (Postgraduate Program, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2025)
The Qur'an is a holy book with beautiful Arabic language, a unique structure, and profound meaning. One form of this beauty is the use of parables (tashbīh) as a means of conveying moral, religious, and legal messages. This style of language not only clarifies meaning but also has a psychological and emotional impact on readers. One of the verses that contains tashbīh is QS. al-Kahf [18]: 45, which describes the transience of the world through the analogy of rainwater that nourishes plants, then dries up and disappears, blown away by the wind. This study combines balāghah analysis, specifically the form tashbīh, with ethical thematic interpretation to pace the parable in this versi as a source of moral values relevant to the modern era. Using the library research method with a descriptive-analytical approach, this study processed primer data in the form of QS. al-Kahf [18]: 45 and secondary data from various classical and contemporary tafsir books. The results showed that tashbīh. This indicates that the world is temporary, constantly changing, a place of trial, and can be beneficial if managed wisely. The moral values contained therein include maintaining balance in life, simplicity, awareness of responsibility, and vigilance against the glamour of the world. These findings confirm the novelty of research in linking Qur'anic rhetoric analysis based on tashbīh with ethical readings that are applicable to spiritual and social life.